Linear-scaling techniques in computational chemistry and physics methods and applications - Zalesny, Robert (Challenges and Advances in Computational Chemistry and Physics, 2011)
Computational chemistry methods have become increasingly important in recent years, as manifested by their rapidly extending applications in a large number of diverse fields. The ever-increasing size of the systems one wants to study leads to the development and application of methods, which provide satisfactory answers at a manageable computational cost. An important variety of computational techniques for large systems are represented by the linear-scaling techniques, that is, by methods where the computational cost scales linearly with the size of the system. This monograph is a collection of chapters, which report the state-of-the-art developments and applications of many important classes of linear-scaling methods. Linear-Scaling Techniques in Computational Chemistry and Physics: Methods and Applications serves as a handbook for theoreticians who are involved in the development of new and efficient computational methods as well as for scientists who use the tools of computational chemistry and physics in their research